RNA Sequence Profiling Reveals Unique Immune and Metabolic Features of Breast Cancer Brain Metastases - Xiao, Limei; Zhou, Jie; Liu, Hongyi; Zhou, Yuanyuan; Chen, Weibin; Cui, Wugeng; Zhao, Yilin (Frontiers in Oncology, 2021)
There is an urgent need to improve our understanding of breast cancer brain metastases (BCBMs). Thus, we obtained gene expression of 19 BCBMs and 19 unmatched nonmetastatic primary breast cancers (BCs) from Gene Expression Omnibus (GEO) database (GSE43837). We identified significant immunosuppression and signatures indicative of immune infiltration in BCBMs, the lower the expression of the signatures, the worse the prognosis of breast cancer patients in KM plotter [Breast cancer] database. We also identified increased oxidative phosphorylation (OXPHOS) utilization in BCBMs compared with BCs and signatures indicative of increased OXPHOS utilization in BCBMs, the higher the expression of the signatures, the worse the prognosis of breast cancer patients in KM plotter [Breast cancer] database, which can predict the prognosis of breast cancer patients better, as it can also predict the prognosis of patients with different breast cancer subtypes in KM plotter [Breast cancer] database. In addition, we obtained gene expression of BCBMs and extracranial metastases (GSE14017 and GSE14018). Compared with extracranial metastases, we identified more significant immunosuppression but no difference in OXPHOS utilization in BCBMs using mRNA sequence. We selected human breast cancer cell line MDA-MB-231 cells as an in vitro cell model, because MDA-MB-231 cells mainly rely on fatty acid oxidation for energy supply. And we confirmed oligomycin, an inhibitor of mitochondrial F(1)F(o)ATPase, substantially attenuated the migration and invasion potential of MDA-MB-231 cells. Our study provides new insights into the pathogenesis of BCBMs.